PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PERKALIAN PADA SISWA KELAS IV SDN TAMBAKSARI III/159 SURABAYA - Anida; Endang Suprapti; Umi Arsiyati (Universitas Muhammadiyah Surabaya, 2024)
The aim of this research is to determine the improvement in learning outcomes of class IV students at SDN Tambaksari III/159 Surabaya through the application of the Problem Based Learning learning model in mathematics subjects, multiplication of whole numbers up to 100. Through this Problem Based Learning learning model, it is hoped that students will become more active. , directly involved in learning, enthusiasm and enthusiasm for participating in learning activities carried out by the teacher. The approach used in this study is a qualitative approach. Meanwhile, the type of research used in this research is classroom action research. Data collection methods consist of observation, tests and documentation. Data analysis techniques are carried out using quantitative and qualitative data analysis techniques. Quantitative data is obtained from the results of students' formative tests at the end of learning. Qualitative data was obtained from observation data regarding the implementation of learning. The research results showed that 13 students scored above the KKTP or 86. 3% of students were declared complete, while 13. 7% had not yet completed. It can be concluded that the Problem Based Learning learning model can improve student learning outcomes in mathematics subjects, multiplication of whole numbers up to 100.